MODERNIZAREA BIBLIOTECILOR PUBLICE: METODE SPECIFICE ÎN CREAREA SERVICIILOR DE BIBLIOTECĂ - BUTUCEL, Elena (BIBLIOPOLIS, 2020)
The concept of modern library is oriented to discovering of new forms of services, new ways of developing, formation, recreation, that increase the rating of libraries in community and attract new segments of users. The evolution of information technologies allows the libraries to develop special services and abilities. The services launch includes the developing of competencies, abilities. The most important elements of library services are information, alphabetization, education and culture. Now, the public library become a framework for realization of community services.